Selective Brain Cooling: A New Horizon of Neuroprotection - Hong, Ji Man; Choi, Eun Sil; Park, So Young (Frontiers in Neurology, 2022)
Therapeutic hypothermia (TH), which prevents irreversible neuronal necrosis and ischemic brain damage, has been proven effective for preventing ischemia-reperfusion injury in post-cardiac arrest syndrome and neonatal encephalopathy in both animal studies and clinical trials. However, lowering the whole-body temperature below 34°C can lead to severe systemic complications such as cardiac, hematologic, immunologic, and metabolic side effects. Although the brain accounts for only 2% of the total body weight, it consumes 20% of the body’s total energy at rest and requires a continuous supply of glucose and oxygen to maintain function and structural integrity. As such, theoretically, temperature-controlled selective brain cooling (SBC) may be more beneficial for brain ischemia than systemic pan-ischemia. Various SBC methods have been introduced to selectively cool the brain while minimizing systemic TH-related complications. However, technical setbacks of conventional SBCs, such as insufficient cooling power and relatively expensive coolant and/or irritating effects on skin or mucosal interfaces, limit its application to various clinical settings. This review aimed to integrate current literature on SBC modalities with promising therapeutic potential. Further, future directions were discussed by exploring studies on interesting coping skills in response to environmental or stress-induced hyperthermia among wild animals, including mammals and birds.